Single-Blind and Double-Blind Peer Review: Effects on National Representation. (2nd January 2022) - Kalavar, Meghana; Watane, Arjun; Wu, David; Sridhar, Jayanth; Mruthyunjaya, Prithvi; Parikh, Ravi
ABSTRACT: Purpose: To assess whether the type of peer-review (single-blinded vs double-blinded) has an impact on nationality representation in journals. Methods: A cross-sectional study analyzing the top 10 nationalities contributing to the number of articles across 16 ophthalmology journals. Results: There was no difference in the percentage of articles published from the journal's country of origin between the top single-blind journals and double-blind journals (SB = 42.0%, DB = 26.6%, p = .49), but there was a significant difference between the percentage of articles from the US (SB = 48.0%, DB = 22.8%, p = .02). However, there was no difference for both country of origin (SB = 38.0%, DB = 26.6%, p = .43) and articles from the US (SB = 35.0%, DB = 22.8%, p = .21) when assessing the top eight double-blind journals matched with single-blind journals of a similar impact factor. The US (n = 16, 100%) and England (n = 16, 100%) most commonly made the top 10 lists for article contribution. This held true even for journals established outside the United States (US=11/12, England = 11/12). Conclusions: There was no significant difference in country-of-origin representation between single-blind journals and double-blind journals. However, higher income countries contributed most often to the journals studied even among journals based outside the US.